CHARACTERISTICS OF EVALUATING THE QUALITY OF OUTSOURCING SERVICES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS BY THE "AMUI" METHOD - Ergasheva, Nasiba Rahmatullayevna (THE INNOVATION ECONOMY, 2024)
In this article, the mechanisms available in the economy, the components of the mechanism of using outsourcing services, including the characteristics of the economic assessment of the quality of outsourcing services based on the "AMUI" (outsourcer, client, third parties, integration) method, based on this, scientifically based suggestions and recommendations on the processes of concluding and managing outsourcing contracts given.